PENGEMBANGAN MADRASAH BERPARADIGMA PEMBANGUNAN BERKELANJUTAN - M Imam Zamroni; Lies Rahayu WF (Jurnal Kawistara, 2012)
This study aims to discover learning innovation for education for sustainable development (EfSD) that canbring sustainability regarding resources, the environmental, social and cultural. EfSD can teach morality tohuman beings as actors in their environment, pushing them to always be careful and wise in every activitythat uses natural resources. The use of natural resources for the development is not only to meet short-termeconomic needs; it is therefore necessary to establish mana gement strategies that ensure sustainability, fairness,and effi ciency. Efforts to achieve these strategies are mediated by interviewing people regarding environmentethical values, which in this case were implemented in children’s education. The results of this research showthat: (1) developing sustainable, development-paradigmatuc learning innovations must comply with the talentsof students, which can be done by developing KTSP (curriculum for unit-level education); (2) the conservationof socio-cultural value is the basis to achieve a sustainable development paradigm; (3) innovations necessaryfor the creation of a sustainable development paradigm vary for each school background. This innovationis expected to guarantee the realization of a sustainable development paradigm in formal education; for thesake of intergenerational environment conservation.